TINJAUAN TENTANG PELAKSANAAN PERJANJIAN ANTARA PT. OYO ROOMS INDONESIA DENGAN DAVONSA HOMESTAY DI JALAN LEMBAGA PEMASYARAKATAN KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Technology and information through applications make it easier for consumers and business owners to meet their desired needs. In this case Davonsa Homestay in cooperation with PT. OYO Rooms Indonesia is a third party application that makes it easier for consumers to find accommodation. However, several problems arose between the PT. OYO Rooms Indonesia in implementing the agreement, with business owner Davonsa Homestay. Based on the above, the draftsman formulates several problems in this study, including: How is the agreement between PT.OYO Rooms Indonesia implemented with Davonsa Homestay? and how the rights and obligations of the parties are to be fulfilled in implementing the agreement between PT. OYO Rooms Indonesia and Davonsa Homestay?The research method or approach used by the author is sociological legal legal research. By sociological legal research, it is meant an approach that looks at the legislative perspective and the realities that arise in the field. Sources for research data are primary and secondary data with descriptive qualitative data analysis methods.The results of this study suggest that the form of a cooperation agreement between PT. OYO Rooms Indonesia with Davonsa Homestay is a standard (standard) where the clauses are set by PT. OYO Rooms Indonesia. In this way, PT. OYO Rooms Indonesia prevents Davonsa Homestay from assuming a profitable negotiating position. And also many problems were found between Davonsa Homestay and PT. OYO Rooms Indonesia. Among other things, PT. OYO Rooms Indonesia is an insufficient reconciliation payment, which means that PT's monthly report matches OYO Rooms Indonesia with monthly reports of Davonsa Homestay, an irrevocable agreement and the waiver of Article 1266 of the Civil Code upon termination of the agreement.Keywords: Cooperation Agreement – Provision of Lodging Services – Rights and Obligations